1992
DOI: 10.1042/bj2850187
|View full text |Cite
|
Sign up to set email alerts
|

Tyr-143 facilitates interdomain electron transfer in flavocytochrome b2

Abstract: The role of Tyr-143 in the catalytic cycle of flavocytochrome b2 (L-lactate:cytochrome c oxidoreductase) has been examined by replacement of this residue with phenylalanine. The electron-transfer steps in wild-type and mutant flavocytochromes b2 have been investigated by using steady-state and stopped-flow kinetic methods. The most significant effect of the Tyr-143----Phe mutation is a change in the rate-determining step in the reduction of the enzyme. For wild-type enzyme the main rate-determining step is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
95
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 22 publications
(38 reference statements)
17
95
1
Order By: Relevance
“…For example, the tetrameric -lactate cytochrome c oxidoreductase (flavocytochrome b # ) from Saccharomyces cere isiae uses Arg-376 and Tyr-143 to stabilize the binding of lactate. The flavocytochrome b # mutant Y143F shows a 6-fold increased K m and an unchanged k cat relative to wild-type using -lactate as a substrate and ferricyanide as the electron acceptor [39,40]. The motif is also conserved in flavocytochrome b # from Hansenula anomala (Arg-362 and Tyr-135) [41] and in the closely related Rhodotorula graminis -mandelate dehydrogenase (Tyr-25 and Arg-277), which is also a tetrameric flavocytochrome [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the tetrameric -lactate cytochrome c oxidoreductase (flavocytochrome b # ) from Saccharomyces cere isiae uses Arg-376 and Tyr-143 to stabilize the binding of lactate. The flavocytochrome b # mutant Y143F shows a 6-fold increased K m and an unchanged k cat relative to wild-type using -lactate as a substrate and ferricyanide as the electron acceptor [39,40]. The motif is also conserved in flavocytochrome b # from Hansenula anomala (Arg-362 and Tyr-135) [41] and in the closely related Rhodotorula graminis -mandelate dehydrogenase (Tyr-25 and Arg-277), which is also a tetrameric flavocytochrome [42].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the presence of Phe312 of Cyc2 at intermediate position between heme C and Asp73 could be presumed an important factor influencing electron transfer from the donor site of heme C to the acceptor site of Asp73 (Figure 2(b)). Previous studies on the cytochromes had clearly demonstrated the significance of phenylalanine/tyrosine residues in mediating electron transfer [58,59]. A close visual inspection of the core region of RcY structure after MD simulation allowed us to observe that several hydrophobic interactions comprising the residues Phe125, Val74, Phe76, Phe54, Phe87, and Trp7 form a channel required for electron transfer to the Cu center (Figure 4(a)).…”
Section: Molecular Interaction Between Cyc2 and Rcy Rcy Is The Intermentioning
confidence: 93%
“…9). This helix is normally rather close to the flavin because Y143 is an active-site residue that forms a hydrogen bond with the substrate carboxylate Miles et al, 1992;Rouviere-Fourmy et al, 1994). Moreover, the two terminal nitrogens in the side chain of R376, another active-site residue, form good hydrogen bonds to the peptide carbonyl group of Y143 and may also interact with the carbonyl oxygen atoms of Y 144 and/or S146.…”
Section: Discussionmentioning
confidence: 99%
“…Y254F mutant proteins, in particular, were studied in detail (Dubois et al, 1990;Miles et al, 1992;Rouvikre-Fourmy et al, 1994). Although their physical properties were not specifically characterized, these mutant enzymes showed no manifest difference with the wild-type protein, either during production in E. coli or throughout purification, storage, and handling.…”
Section: Gondry Ef Almentioning
confidence: 99%